Multi-proxy analyses of a minerotrophic fen to reconstruct prehistoric periods of human activity associated with salt mining in the Hallstatt region (Austria). (April 2021) - Knierzinger, Wolfgang; Festi, Daniela; Limbeck, Andreas; Horak, Felix; Brunnbauer, Lukas; Drollinger, Simon; Wagreich, Michael; Huang, Jyh-Jaan Steven; Strasser, Michael; Knorr, Klaus-Holger; Reschreiter, Hans; Gier, Susanne; et al.
Highlights: Intense human activity between ~1300 cal BCE and ~500 cal BCE. High Sn concentrations imply bronze casting between ~1210 cal BCE ~540 cal BCE. Early periods of moderate human impact around ~2350 cal BCE and ~1800 cal BCE. Distinct isotopic signature of peat underlines the local origin of signals. Abstract: In this study, periods of prehistoric anthropogenic activity in the Hallstatt salt mining area (Upper Austria) are reconstructed from elemental (XRF-scanning, Q-ICP-MS) and Pb isotopic analyses ( 206 Pb, 207 Pb, 208 Pb) of a radiocarbon-dated, 137-cm-long peat core covering the past ~7, 000 years. The peat core was retrieved from a minerotrophic fen in the Hallstatt High Valley. Distinct metal enrichments attributed to low anthropogenic impact in Hallstatt can be traced back to a time around 2350 cal BCE and to another period around 1800 cal BCE. The period from the Late Bronze Age to the Early Iron Age (~1300 cal BCE to ~500 cal BCE) is characterised by increased anthropogenic activity. Relatively high Sn concentrations between ~1210 cal BCE and ~540 cal BCE) point towards intensive bronze casting processes, probably associated with the production of bronze picks that were used for local salt mining during this time. Intense human impact was also determined for the early Roman imperial period (1st century BCE – 2nd century CE). Increasing Pb and Sb concentrations and a marked decrease of 206 Pb/ 207 Pb ratios in the uppermost fen layers are attributed to rising industrialization processes in the modern period. Even though peaks of the trace elements Pb, Sb, Cu and Sn do not always correspond directly to anthropogenic activity, a combination with erosional, archaeological and palaeovegetational records enables a relatively accurate and reliable interpretation of prehistoric human impact at Hallstatt.